DMSNs@Ce-ZIF-67 composite material for silicone rubber and preparation method thereof

By using an amyotrophic dendritic silica support in silicon rubber to grow cerium ion-doped ZIF-67 in situ, the DMSNs@Ce-ZIF-67 composite material is formed, which solves the problem of limited application of silicon rubber in extreme environments and significantly improves its thermal oxygen aging resistance.

CN115975260BActive Publication Date: 2025-04-04CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310036328.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-09
Publication Date
2025-04-04
Estimated Expiration
2043-01-09

AI Technical Summary

Technical Problem

The existing silicone rubber materials are limited in application in extreme environments, have insufficient thermal oxygen aging performance, and traditional heat-resistant fillers have poor dispersion and compatibility in silicone rubber matrix, resulting in reduced material performance and waste of resources.

Method used

Aminized dendritic silica is used as a support to grow cerium ion-doped ZIF-67 in situ to form a DMSNs@Ce-ZIF-67 composite material as a functional nanofiller for silicone rubber to improve the compatibility and heat resistance of the material.

Benefits of technology

By using DMSNs@Ce-ZIF-67 composite material, the initial degradation temperature of silicone rubber is greatly improved, and the thermal oxygen aging performance is significantly improved. Compared with traditional iron oxides and cerium oxides, it has better reinforcement and comprehensiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004044797440000111
    Figure BDA0004044797440000111
  • Figure BDA0004044797440000112
    Figure BDA0004044797440000112
  • Figure HDA0004044797450000011
    Figure HDA0004044797450000011
Patent Text Reader

Abstract

The present invention belongs to the technical field of silicone rubber, and specifically discloses a DMSNs@Ce‑ZIF‑67 composite material for silicone rubber and a preparation method thereof. Dendritic silica (DMSNs) is first prepared and used as a carrier. After amino groups are modified on the surface of the dendritic silica, cerium ion-doped ZIF‑67 (Ce‑ZIF‑67) is in situ grown in the pores of the dendritic silica to obtain a composite material, which can better improve the heat-resistant oxygen aging performance of silicone rubber at a small filling number. The sacrifice of comprehensive mechanical properties brought about by high heat-resistant filler concentration is alleviated, and a new strategy is provided for the functionalization of fillers in silicone rubber composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicone rubber, and specifically relates to a DMSNs@Ce-ZIF-67 composite material for silicone rubber and a preparation method thereof. Background Art

[0002] The aging of elastomers is usually determined by the combined effects of internal and external factors, and is manifested as stickiness, hardening, powdering, softening, and cracking. Silicone rubber is widely used in electronics, biomedicine, aerospace, and other fields due to its Si-O-Si structure. However, technological development has put forward higher requirements for it, and its application in extreme environments is limited.

[0003] The process of improving the heat-resistant and oxygen-aging resistance of silicone rubber includes modification of the main and side chains. The most common method is to inhibit the oxidation cross-linking of the side chains and the cyclization degradation of the main chain by adding heat-resistant fillers. Traditional heat-resistant additives mainly include metals, metal oxides, polymers, carbon materials, etc. The requirements of the heat-resistant system are often met by stacking high fillers. However, a large amount of heat-resistant fillers (Fe2O3, CeO2, ZnO, etc.) need to face problems such as dispersibility and compatibility in the silicone rubber matrix. The large-scale use of heavy metals is not only a pollution to the environment, but also a waste of the material itself.

[0004] MOF is a new type of material that combines metal ions with organic ligands, and has the advantages of high specific surface area and low density. 2+ ions and imidazole, which are easy to prepare and rich in C and N elements. Co ions can absorb and dissociate external oxygen in Co 2+ and Co 3+ The doped Ce ions can create more oxygen vacancies and adsorb more oxygen, so Ce-ZIF-67 is an excellent free radical scavenger, but MOF materials have rarely been reported to be used in silicone rubber.

[0005] Generally, inorganic nanomaterials and organic polymers are not compatible. Dendritic silica is modified by coupling agent KH-550 to improve the compatibility of the material as a filler in silicone rubber (Chemical Engineering Journal, 2018-08-15, Vol. 346, pp. 497-505). However, mesoporous silica has a small pore size distribution and is prone to blockage during material transport (Polumers for Advanced Technologies, 2021-06-08, Vol. 32, No. 9, pp. 3384-3391). Summary of the invention

[0006] In order to improve the sacrifice of comprehensive mechanical properties and waste of materials of silicone rubber composite materials caused by excessive heat-resistant fillers, the present invention provides a novel porous nano filler, which can significantly increase the initial degradation temperature of silicone rubber composite materials by only filling a small amount.

[0007] The first technical problem to be solved by the present invention is to provide a low-fraction heat-resistant functional nanocomposite material, which uses amino-modified dendritic silica as a carrier and in-situ grows cerium-doped ZIF-67 in the pores of the dendritic silica. Aminated dendritic silica can be used as a mechanical reinforcement filler for silicone rubber on the one hand, and can enhance the compatibility between nanomaterials and silicone rubber on the other hand. The doped cerium ions can cause more oxygen vacancies to be generated on the crystal surface, accelerating the redox reaction rate inside the silicone rubber.

[0008] The diameter of the dendritic silica is 200 to 500 nm, and the pore size distribution is 2 to 32 nm.

[0009] Preferably, the particle size of the dendritic silica is 300-400 nm.

[0010] The obtained dendritic silica in-situ loaded cerium ion doped ZIF-67 nanomaterial has a narrow particle size distribution and controllable size, and can be applied to functional nanofillers of silicone rubber.

[0011] The second technical problem to be solved by the present invention is to provide a method for preparing dendritic silica in situ loaded with cerium ion-doped ZIF-67 nanofiller. The size and pore size of the dendritic silica prepared by the method are adjustable, and the cerium ion-doped ZIF-67 has a good morphology and a narrow particle size distribution. At the same time, it exhibits good dispersibility in the silicone rubber matrix.

[0012] The preparation method of ZIF-67 composite silicone rubber doped with cerium ions in situ loaded by dendritic silica comprises the following steps:

[0013] 1) Disperse triethanolamine in water, heat and stir at 80°C, add hexadecyltrimethylammonium bromide and sodium salicylate, continue stirring for 0.5-1 hour, then add ethyl orthosilicate and react for 1-3 hours; finally, centrifuge and wash, disperse in hydrochloric acid / methanol solution, stir at 60°C for 3-6 hours to remove the template, centrifuge at 10000-12000 rpm for 6-12 minutes and dry overnight to obtain dendritic silica.

[0014] Among them, the amount of triethanolamine used is 85mg~200mg, the amount of hexadecyltrimethylammonium bromide used is 312mg~500mg, the amount of sodium salicylate used is 289mg~450mg, the amount of tetraethyl orthosilicate used is 1~8mL, and the amount of hydrochloric acid / methanol solution used is 30mL, wherein the ratio of the volume of hydrochloric acid to the volume of methanol is 1:9.

[0015] 2) Dissolve the dendritic silica obtained in step 1) in a toluene solution, add a coupling agent, reflux and stir at 60-80° C. for 3-4 hours, centrifuge at 8000-10000 rpm for 5-10 minutes and dry overnight.

[0016] The amount of dendritic silica used is 400-500 mg, and the amount of coupling agent used is 0.4 mL-0.6 mL.

[0017] The coupling agent is selected from one or more of KH-540, KH-550, KH792, and KH602.

[0018] 3) The aminated dendritic silica obtained in step 2) is dispersed in a mixed solution of cobalt nitrate hexahydrate and cerium nitrate hexahydrate, and dispersed by ultrasonic stirring for 0.5 to 2 hours, and then slowly added dropwise to a dimethylimidazole solution, stirred at room temperature for 18 to 24 hours, and dried by centrifugation at 8000 to 10000 rpm for 5 to 10 minutes to obtain a DMSNs@Ce-ZIF-67 composite material.

[0019] The amount of amino-modified dendritic silica is 150 mg to 200 mg, the molar ratio of Ce(NO3)3·6H2O to dimethylimidazole is 1:40 to 1:60, and the molar ratio of Co(NO3)2·6H2O to dimethylimidazole is 1:5 to 1:7.

[0020] The concentration of dimethylimidazole is 0.25~0.375mol / L.

[0021] The third technical problem to be solved by the present invention is the thermal oxygen aging resistance of silicone rubber by ZIF-67 material doped with cerium ions loaded with dendritic silica.

[0022] The DMSNs@Ce-ZIF-67 composite nanofiller, white carbon black and high temperature vulcanized silicone rubber were mixed for 10 to 20 minutes, and then the vulcanizing agent was added and mixed on a roller until uniform, and then poured into a mold and cured at 120 to 175°C for 15 to 30 minutes.

[0023] Among them, the dendritic silica carries 0.25 to 1.5 parts by weight of ZIF-67 material doped with cerium ions, white carbon black is 20 to 30 parts by weight, high temperature vulcanized silicone rubber is 100 parts by weight, and a vulcanizing agent is 1 to 3 parts by weight.

[0024] Preferably, the high temperature vulcanized silicone rubber is selected from one or more of methyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber or methyl trifluoropropyl silicone rubber.

[0025] The vulcanizing agent is selected from one or more of benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl perbenzoate, di-tert-butyl peroxide, diisopropylbenzene peroxide or 2,5-dimethyl, 5-di-tert-butyl peroxide hexane.

[0026] Beneficial effects of the present invention:

[0027] The present invention provides a DMSNs@Ce-ZIF-67 composite material for heat-resistant silicone rubber and a preparation method thereof. Ce-ZIF-67 is in situ loaded on the amino dendritic silica. The amino silica as a carrier alleviates the compatibility problem between inorganic materials and silicone rubber. The oxygen vacancies caused by the bimetal accelerate the valence state transition between metal ions and capture the side chain free radicals of silicone rubber. The synergistic effect between the bimetals can better improve the heat resistance of silicone rubber, and has better comprehensive reinforcement than traditional iron oxide and cerium oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a transmission electron microscopy image of DMSNs@Ce-ZIF-67 prepared in Example 1 at a scale of 200 nm;

[0029] Figure 2 Zeta potential diagram of DMSNs and DMSNs-NH2 prepared in Example 1;

[0030] Figure 3 XRD spectra of prepared ZIF-67, Ce-ZIF-67 and DMSNs@Ce-ZIF-67;

[0031] Figure 4 TG graphs of the prepared DMSNs@Ce-ZIF-67 and Ce-ZIF-67 after vulcanization with methyl vinyl silicone rubber.

[0032] Figure 5 The mechanical property retention rates of the nanocomposites prepared in Examples 1, 4, 5, 6 and 7 and methyl vinyl silicone rubber before and after thermal oxidative aging after vulcanization. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect. The experimental methods used in the following examples are conventional methods unless otherwise specified; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.

[0034] Example 1

[0035] (1) 128 mg of triethanolamine was added to 25 mL of water and stirred at 80°C for 0.5 hours, and then 456 mg of hexadecyltrimethylammonium bromide and 394 mg of sodium salicylate were added and stirred for 1 hour, and then 4 mL of ethyl orthosilicate was added dropwise and stirred for 2 hours. The mixture was centrifuged at 12000 rpm for 6 minutes, dispersed in 30 mL of hydrochloric acid / methanol solution (volume ratio of hydrochloric acid to methanol was 3:1), refluxed at 60°C for 6 hours, and dried to obtain dendritic silica.

[0036] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0037] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.6×10 - 2 mol / L cobalt nitrate hexahydrate and 40mL of 6.25×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0038] (4) After kneading 1 part by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0039] from Figure 1 It can be clearly observed that the prepared DMSNs@Ce-ZIF-67 has a small particle size distribution range, with a diameter of about 300nm, and Ce-ZIF-67 as the "core" is limited to about 20nm in the pore size. It can be clearly seen from the transmission image that the obtained material is a core-shell structure. Figure 4 It can be seen from Tables 1 and 2 that the heat-oxidative aging resistance of Example 1 is greatly improved.

[0040] Example 2

[0041] (1) The preparation of dendritic silicon dioxide was the same as in Example 1.

[0042] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0043] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.9×10 - 2 mol / L cobalt nitrate hexahydrate solution and 40mL of 3.1×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0044] (4) After kneading 1 part by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0045] Example 3

[0046] (1) The preparation of dendritic silicon dioxide was the same as in Example 1.

[0047] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0048] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.3×10 - 2 mol / L cobalt nitrate hexahydrate solution and 40mL of 9.4×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0049] (4) After kneading 1 part by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0050] Example 4

[0051] (1) The preparation of dendritic silicon dioxide was the same as in Example 1.

[0052] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0053] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.6×10 - 2 mol / L cobalt nitrate hexahydrate and 40mL of 6.25×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0054] (4) After kneading 0.25 parts by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0055] Example 5

[0056] (1) The preparation of dendritic silicon dioxide was the same as in Example 1.

[0057] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0058] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.6×10 - 2 mol / L cobalt nitrate hexahydrate and 40mL of 6.25×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0059] (4) After kneading 0.5 parts by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0060] Example 6

[0061] (1) The preparation of dendritic silicon dioxide was the same as in Example 1.

[0062] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0063] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.6×10 - 2 mol / L cobalt nitrate hexahydrate and 40mL of 6.25×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0064] (4) After kneading 0.75 parts by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0065] Example 7

[0066] (1) The preparation of dendritic silicon dioxide was the same as in Example 1.

[0067] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0068] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.6×10 - 2 mol / L cobalt nitrate hexahydrate and 40mL of 6.25×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0069] (4) After kneading 1.5 parts by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0070] Example 8

[0071] (1) The preparation of dendritic silicon dioxide was the same as in Example 1.

[0072] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0073] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.6×10 - 2 mol / L cobalt nitrate hexahydrate and 40mL of 6.25×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0074] (4) After kneading 1 part by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was rolled and pressed until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0075] Example 9

[0076] (1) The preparation of dendritic silicon dioxide was the same as in Example 1.

[0077] (2) 500 mg of the dendritic silica prepared in step 1) was dissolved in 100 mL of toluene, 0.5 mL of KH-550 was added, the mixture was refluxed at 80° C. for 4 hours, centrifuged at 10,000 rpm for 5 minutes, and dried overnight.

[0078] (3) 150 mg of the amino-modified dendritic silica prepared in step 2) was dispersed in 40 mL of a 5.6×10 - 2 mol / L cobalt nitrate hexahydrate and 40mL of 6.25×10 -3 mol / L cerium nitrate hexahydrate solution, ultrasonically stirred for 1.5 hours, slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0079] (4) After kneading 1 part by mass of the filler powder obtained in step 3), 30 parts by mass of white carbon black and 100 parts by mass of methylphenyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was rolled on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0080] Comparative Example 1

[0081] Silicone rubber material without adding MOF composite filler.

[0082] Comparative Example 2

[0083] (1) 0.5 mL of silane coupling agent KH-550 was added dropwise to 40 mL of anhydrous methanol aqueous solution, wherein the volume ratio of anhydrous methanol to water was 2:1, and the coupling agent was added for hydrolysis for 10 minutes.

[0084] (2) The solution obtained in step 1) was added dropwise into a three-necked flask containing 100 mg of red iron oxide powder, and 100 mL of anhydrous methanol was added. The three-necked flask was connected to a condenser, stirred at 80° C. for 2 h, and dried overnight.

[0085] (3) After kneading 1 mass part of the filler powder obtained in step 2), 30 mass parts of white carbon black and 100 mass parts of methyl vinyl silicone rubber for 20 minutes, 2 mass parts of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0086] Comparative Example 3

[0087] (1) 40 mL of a 5.6×10 -2 mol / L cobalt nitrate hexahydrate and 40mL of 6.25×10 -3 mol / L cerium nitrate hexahydrate solution was slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0088] (2) After kneading 1 part by mass of the filler powder obtained in step 1), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0089] Comparative Example 4

[0090] (1) 80 mL of a 6.2×10 -2 mol / L cobalt nitrate hexahydrate was slowly added into 80mL of 0.375mol / L dimethylimidazole solution, stirred at room temperature for 24 hours, centrifuged at 10000rpm for 5 minutes and dried overnight.

[0091] (2) After kneading 1 part by mass of the filler powder obtained in step 1), 30 parts by mass of white carbon black and 100 parts by mass of methyl vinyl silicone rubber for 20 minutes, 2 parts by mass of benzoyl peroxide were added, the mixture was pressed on a roller until uniform, and then poured into a mold and cured at 150° C. for 15 minutes to prepare a silicone rubber composite material.

[0092] The thermal oxidative aging test standard is GB / T 3512-2001 vulcanized rubber or thermoplastic rubber heating aging and heat resistance test.

[0093] The tensile strength test standard is GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber.

[0094] Table 1 is a comparison of the tensile strength of the silicone rubber composite materials prepared in each embodiment and comparative example before and after thermal oxidation aging.

[0095] Table 2 shows the average molecular weight of the rubber before and after the thermal aging test after the DMSNs@Ce-ZIF-67, Ce-ZIF-67, and Fe2O3 prepared in the examples were vulcanized with silicone rubber.

[0096] Table 1 Comparison of mechanical properties before and after thermal oxidation aging

[0097]

[0098] Table 2 Comparison of average molecular weight of rubber before and after thermal oxidation aging

[0099]

Claims

1. An application of a DMSNs@Ce-ZIF-67 composite material, characterized in that: The DMSNs@Ce-ZIF-67 composite material, white carbon black and high temperature vulcanized silicone rubber were mixed, and a vulcanizing agent was added to cure the silicone rubber composite material; The preparation steps of the DMSNs@Ce-ZIF-67 composite material are as follows: 1) Dispersing dendritic silica in a toluene solution, then adding a coupling agent, stirring under reflux, centrifuging, and drying overnight to obtain amino dendritic silica; 2) dispersing the amino-modified dendritic silica prepared in step 1) in a mixed solution of Ce(NO3)3·6H2O and Co(NO3)2·6H2O, and stirring uniformly by ultrasonication; 3) The mixed solution obtained in step 2) is added dropwise to the dimethylimidazole solution, stirred at room temperature, centrifuged for washing, and dried overnight to obtain a composite material.

2. The use of the DMSNs@Ce-ZIF-67 composite material according to claim 1, characterized in that: The amount of white carbon black is 20-30 parts by mass, the amount of DMSNs@Ce-ZIF-67 composite material is 0.25-1.5 parts by mass, the amount of high temperature vulcanized silicone rubber is 100 parts by mass, and the amount of vulcanizing agent is 1-3 parts by mass.

3. The use of the DMSNs@Ce-ZIF-67 composite material according to claim 2, characterized in that: The vulcanizing agent is selected from one or more of benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, tert-butyl perbenzoate, di-tert-butyl peroxide, and dicumyl peroxide; the high temperature vulcanized silicone rubber is selected from one or more of methyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, or methyl trifluoropropyl silicone rubber.

4. The use of the DMSNs@Ce-ZIF-67 composite material according to claim 1, characterized in that: The vulcanization temperature is 120-175° C., and the curing time is 15-30 minutes.

5. The use of the DMSNs@Ce-ZIF-67 composite material according to claim 1, characterized in that: In step 1), the amount of dendritic silica used is 400-500 mg, the amount of coupling agent used is 0.4-0.6 mL, the reflux temperature is 60-80°C, and the stirring time is 3-4 hours.

6. The use of the DMSNs@Ce-ZIF-67 composite material according to claim 1, characterized in that: In step 1), the coupling agent is selected from one or more of KH-540, KH-550, KH792, and KH602.

7. The use of the DMSNs@Ce-ZIF-67 composite material according to claim 1, characterized in that: In step 2), the amount of amino-modified dendritic silica is 150 mg~200 mg, the molar ratio of Ce(NO3)3·6H2O to dimethylimidazole is 1:40~1:60, and the molar ratio of Co(NO3)2·6H2O to dimethylimidazole is 1:5~1:

7.

8. The use of the DMSNs@Ce-ZIF-67 composite material according to claim 1, characterized in that: In step 3), the concentration of dimethylimidazole is 0.25-0.375 mol / L, stirred at room temperature for 18-24 hours, and centrifuged at 8000 rpm-11000 rpm for 5-10 minutes.